Healthy behaviours, treatment, and control status of diagnosed hypertension and diabetes among the government nurses and para-health professionals of Bangladesh: A cross-sectional study. - Lingkan Barua; Palash Chandra Banik; Mithila Faruque (Public Library of Science (PLoS), 2023)
Chronic illness among health professionals (HPs) is rarely reported due to idealistic views of their role in treating and fighting diseases. This creates a gap mainly due to a lack of research on them, resulting in insufficient data at the national level, especially in Bangladesh. In this circumstance, we analyzed the data of senior staff nurses (SSNs) and para-health professionals (PHPs) to assess their healthy bahaviours, treatment, and control status of hypertension (HTN) and diabetes mellitus (DM). It was a cross-sectional study that used the census as a sampling technique. The study site was a medical university in Bangladesh located in the capital city of Dhaka. A total of 1942 government-employed health professionals working at Upazila Health Complexes participated and completed both the questionnaire and physical measurements with a response rate of 100%. Among them, 1912 (SSNs = 938 and PHPs = 974) remained for analysis after data cleaning. The prevalence of self-screening (HTN, 97.4%; DM, 81.5%), diagnosis (HTN, 20.5%; DM,15.3%), treatment (HTN, 88.7%; DM, 83.7%) and control status (HTN, 63.7%; DM, 31%) did not reveal any notable differences between SSNs and PHPs. Most of the HPs with HTN and DM failed to maintain adequate physical activity (87.4%; 86.2%), fruit and/or vegetable intake (60.7%; 59%), and healthy body weight (60.5%; 54%) respectively. Only avoidance of smoking showed a significant association with the professional categories in both hypertensives (AOR, 7.98; p = 0.001) and diabetics (AOR, 14.78; p<0.001). Although working in the field of primary health care and involved in assisting patient management, control of HTN, DM and their risk factors is not satisfactory among the SSNs and PHPs of Bangladesh. Future interventions should focus on smoking, diet, and physical activity to reduce HTN and DM in the HPs of Bangladesh.